Therapeutic leukocytapheresis in infants and children with leukemia and hyperleukocytosis: A single institution experience. Issue 3 (29th November 2017) - Thapa, Namisha; Pham, Robin; Cole, Charles; Meinershagen, Mitchell; Bowman, Paul W.; Ray, Anish
Abstract : Background: Hyperleukocytosis, defined as white blood cell (WBC) count above 100 × 10 9 /L, has high early morbidity and mortality from leukostasis‐related complications, namely intracranial hemorrhage and pulmonary distress. Initiating chemotherapy without prior leukocytoreduction may lead to tumor lysis syndrome (TLS). Therapeutic leukocytapheresis (TL) is used as one leukocytoreductive intervention; however, its safety and efficacy in pediatric leukemia has not been established. The purpose of this study is to evaluate safety of TL in pediatric patients and assess the efficacy of TL in reducing WBC count in pediatric leukemia. Methods: Retrospective chart review was conducted on 14 patients with acute lymphoblastic leukemia (ALL) and 5 with acute myeloid leukemia (AML) who underwent TL during the period 2000‐2014 at a single institution. Results: Mean WBC count of 19 patients who received TL was 483.2 × 10 9 /L (547.1 in ALL, 304.3 in AML); a portion of patients presented with central nervous system symptoms (15%), respiratory symptoms (10%), or both (10%). TL reduced WBC count (mean 50.7% reduction after a single TL procedure; additional 17.1% reduction after a second TL procedure in 6 patients). Short‐term survival immediately following TL was 100% without any major procedural complication. Mean survival time in patients with AML was 1.5 years and with ALL was 6.5 years. Conclusions: TL significantly reduces WBC number in pediatric leukemia patients as young as 22 days old. In our retrospective study, TL was not associated with any significant complications and suggests that TL is a safe initial procedure in pediatric leukemia.